Take a deep dive Into your bowl of beans: New discoveries using multi-omics research methods - Kennedy, Gina (2025)
Worldwide, beans are well-known nutritionally as a good source of carbohydrates, protein, iron, zinc and dietary fiber, while also being low in fat. These properties make beans an excellent choice for plant-based protein and dietary fiber. Beans also provide food security for many communities. Environmentally, beans are known for nitrogen fixation and performing well in inter-cropped systems.